The Role of Social Support in Identity Processes and Posttraumatic Growth: A Study of Victims of Intimate Partner Violence - Žukauskienė, Rita (Journal of interpersonal violence, 2021)
The purpose of this study was to explore the role of social support for posttraumatic growth (PTG) and identity processes in a sample of 217 women victims of intimate partner violence (IPV), recruited from women shelters, social support centers, and through counseling psychologists. The results of the study highlight the important role of social support in seeking positive personal resolutions after experiencing traumatic events of IPV. It indicates that social support, but not social nonsupport, predicts higher levels of PTG and the development of new positive identities. In particular, social support was positively associated with the manifestation of all five identity processes, that is, with identification with commitment, commitment making, exploration in breadth, exploration in depth, and ruminative exploration. Furthermore, contextual and socioeconomic factors, such as time after last violence, relationships with the perpetrator, place of residence, education, and age of the victims of IPV were also related to identity processes. Severity of the violence, time after the last violence, education, and personal income were related to PTG. Thus, this study indicated that there are significant contextual and socioeconomic differences in the PTG and reconsideration of one’s identity. Recommendations for practitioners and future research have been suggested.